2017
DOI: 10.1007/s00338-017-1569-6
|View full text |Cite
|
Sign up to set email alerts
|

Changes in mesophotic reef fish assemblages along depth and geographical gradients in the Northwestern Hawaiian Islands

Abstract: Mesophotic coral ecosystems (MCEs) extend from 30 to 150 m in depth and support diverse communities of marine organisms. We investigated changes in the structure of mesophotic reef fish assemblages (27-100 m) in the Northwestern Hawaiian Islands (NWHI) along depth and geographical gradients using open-and closed-circuit trimix diving. There were clear changes in the assemblage structure from the southeastern to the northwestern end of the NWHI and from shallow to deep waters. Interactive effects of depth and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…In all areas except Area 2, community analyses and spatial models indicated that average species richness (and abundance) was lower on the AC125 than in adjacent shallower sites off the AC125, and higher on the AC125 than in adjacent deeper sites off the AC125. These findings are consistent with patterns of decline in richness with increasing depth reported elsewhere across tropical marine taxa [ 1 , 11 , 79 81 ]. In Area 2, a greater number of species and individuals was observed on the AC125 than off the AC125, which is likely linked to its proximity to the biodiverse Rankin Bank.…”
Section: Discussionsupporting
confidence: 91%
“…In all areas except Area 2, community analyses and spatial models indicated that average species richness (and abundance) was lower on the AC125 than in adjacent shallower sites off the AC125, and higher on the AC125 than in adjacent deeper sites off the AC125. These findings are consistent with patterns of decline in richness with increasing depth reported elsewhere across tropical marine taxa [ 1 , 11 , 79 81 ]. In Area 2, a greater number of species and individuals was observed on the AC125 than off the AC125, which is likely linked to its proximity to the biodiverse Rankin Bank.…”
Section: Discussionsupporting
confidence: 91%
“…As nearshore sampling sites were shallower and offshore sites were deeper it was not possible to separate the influence of depth from distance to shore. Most studies found depth to be the primary predictor of species richness [48][49][50][51][52] . One of these studies did show that following depth, distance to shore was the next most significantly related variable to assemblage structure 49 .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, several studies have found that lower MCEs (∼60-150 m) also support fish assemblages distinct from upper MCEs and shallower habitats (Kahng et al, 2017;Semmler et al, 2017;Sih et al, 2017), suggesting even greater partitioning than previously thought. These assemblages are typified by the increased occurrence of endemic or undescribed species with increasing depth (Kane et al, 2014;Fukunaga et al, 2017;Kosaki et al, 2017) and thus warrant sustainable management and conservation in themselves. With a few exceptions (Colin, 1976;Thresher and Colin, 1986;Love et al, 2009;Starr et al, 2012;Sih et al, 2017), less is known about assemblages in deeper habitats (>150 m) from tropical and sub-tropical locations.…”
Section: Introductionmentioning
confidence: 99%